Організація та проведення ярмаркової торгівлі на Правобережній Україні у другій половині ХІХ – на початку ХХ ст.: соціонормативний і документаційний аспект - Горова, В. (Краєзнавство, 2022)
У статті висвітлюється нормативне та документаційне забезпечення ярмаркової торгівлі на Правобережній Україні у другій половині ХІХ - на початку ХХ ст. Розкрито групи офіційних документів органів державної влади, якими регулювались питання торгівлі у містах, містечках і селах Київської, Подільської і Волинської губерній. Визначено види документів, особливості складання їх текстової частини, формуляру, склад основних реквізитів. Встановлено порядок відкриття ярмарків, їх перенесення на інші дні чи у інше місце, а також названі органи влади, які мали компетенцію у цих питаннях. The article deals with normative, legal and document regulations of the fair trade on the Right- Bank Ukraine in the second half of the 19th - early 20th centuries. The public authorities’ documents that regulated trade in cities, towns and villages of the Kyiv, Podil and Volhynia provinces have been revealed. Identified are the types of documents, peculiarities of their composition, record cards formation, and the structures of the main requisites. Determined is the procedure of fairs opening, the dates and places the fairs were held. Displayed are the authorities entitled to perform all these operations. Investigation of normative legal and documentary aspects of organization and order of conducting traditional elections on the territory of Right-Bank Ukraine in the 19tn - early 20th century sets the task of in-depth study of archival sources. An extensive array of archival materials provides an opportunity to analyze normative legal documents of state authorities which were used for regulating trade issues in the cities, towns and villages of Kyiv, Podil and Volyn provinces. The purpose of a thorough analysis of official documentation on fairs, bazaars in the region is to determine the types (separate groups) of documents, the peculiarities of compiling their text part, the description of the form of the document, the composition of the basic details, etc. The decisions on the organization of internal trade in the region will make it possible to determine the peculiarities of this process. Fair trade in the Right-Bank Ukraine in the second half of the nineteenth and early twentieth centuries was clearly organized, took place with permission of the authorities, and was regulated by the following documents: the regulations and resolutions of the Provincial Executive and the City Duma, the decision of the City Duma, minutes of the City Duma, letters of request (petition), letters of reply, reports of Podolsky, Kiev and Volyn governors, reports of county executives, lists of bids and fairs that existed in the provinces, announcements about holding fairs that were normative and organizational and administrative.